Chasing Gold: Heat Acclimation in Elite Handcyclists with Spinal Cord Injury - Lackner, Mike; Grossmann, Fabian; Perret, Claudio; Flueck, Joelle L; Hertig-Godeschalk, Anneke (International Journal of Sports Medicine, 2024)
Thermoregulation is impaired in individuals with a spinal cord lesion (SCI), affecting sweat capacity, heat loss, and core temperature. This can be particularly problematic for athletes with SCI who exercise in hot and humid conditions, like those during the Tokyo 2020 Paralympic Games. Heat acclimation can support optimal preparation for exercise in such challenging environments, but evidence is limited in endurance athletes with SCI. We evaluated whether seven consecutive days of exercise in the heat would result in heat acclimation. Five elite para-cycling athletes with SCI participated (two females, three males, median (Q1-Q3) 35 (31–51) years, four with paraplegia and one with tetraplegia). All tests and training sessions were performed in a heat chamber (30°C and 75% relative humidity). A time-to-exhaustion test was performed on day 1 (pretest) and day 7 (posttest). On days 2–6, athletes trained daily for one hour at 50–60% of individual peak power (PPeak). Comparing pretest and posttest, all athletes increased their body mass loss (p=0.04), sweat rate (p=0.04), and time to exhaustion (p=0.04). Effects varied between athletes for core temperature and heart rate. All athletes appeared to benefit from our heat acclimation protocol, helping to optimize their preparation for the Tokyo 2020 Paralympic Games.
Keywords: heat chamber; endurance performance; thermoregulation; Paralympics; paraplegia; tetraplegia; para-athletes